Using community informatics to transform regions - Marshall, Stewart.; Taylor, Wallace, 1944-; Yu, Xing Huo. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2004)
In many international settings, regional economies are declining resulting in lowered opportunities for these communities. This result attacks the very fabric of cohesion and purpose for these regional societies, and increases social, health, economic and sustainability problems. Community informatics research, education and practice is an emerging area in many countries, which seeks to address these issues. The primary objective of this book is to provide leaders, policy developers, researchers, students and community workers with successful strategies and principles of Community Informatics to transform regions. It embraces an integrative cross-sectoral approach in the use of Community Informatics to increase both social and cultural capital as a means to increased sustainability for regional communities.